Chemogenetic Manipulations of Ventral Tegmental Area Dopamine Neurons Reveal Multifaceted Roles in Cocaine Abuse - Mahler, Stephen V. (J Neurosci, 2019)
Ventral tegmental area (VTA) dopamine (DA) neurons perform diverse functions in motivation and cognition, but their precise roles in addiction-related behaviors are still debated. Here, we targeted VTA DA neurons for bidirectional chemogenetic modulation during specific tests of cocaine reinforcement, demand, and relapse-related behaviors in male rats, querying the roles of DA neuron inhibitory and excitatory G-protein signaling in these processes. Designer receptor stimulation of G(q) signaling, but not G(s) signaling, in DA neurons enhanced cocaine seeking via functionally distinct projections to forebrain limbic regions. In contrast, engaging inhibitory G(i/o) signaling in DA neurons blunted the reinforcing and priming effects of cocaine, reduced stress-potentiated reinstatement, and altered behavioral strategies for cocaine seeking and taking. Results demonstrate that DA neurons play several distinct roles in cocaine seeking, depending on behavioral context, G-protein-signaling cascades, and DA neuron efferent targets, highlighting their multifaceted roles in addiction. SIGNIFICANCE STATEMENT G-protein-coupled receptors are crucial modulators of ventral tegmental area (VTA) dopamine neuron activity, but how this metabotropic signaling impacts the complex roles of dopamine in reward and addiction is poorly understood. Here, we bidirectionally modulate dopamine neuron G-protein signaling with DREADDs (designer receptors exclusively activated by designer drugs) during a variety of cocaine-seeking behaviors, revealing nuanced, pathway-specific roles in cocaine reward, effortful seeking, and relapse-like behaviors. G(q) and G(s) stimulation activated dopamine neurons, but only G(q) stimulation robustly enhanced cocaine seeking. G(i/o) inhibitory signaling reduced some, but not all, types of cocaine seeking. Results show that VTA dopamine neurons modulate numerous distinct aspects of cocaine addiction- and relapse-related behaviors, and point to potential new approaches for intervening in these processes to treat addiction.